Investigating time‐of‐flight spin‐echo modulation for small‐angle neutron scattering through experiments and simulation. (1st February 2015) - Sales, Morten; Plomp, Jeroen; Habicht, Klaus; Strobl, Markus
<x xml:space="preserve">Abstract</x> A spin‐echo‐modulated small‐angle neutron scattering (SEMSANS) instrument in a time‐of‐flight (TOF) mode will be able to excel at pulsed neutron sources such as the European Spallation Source (ESS), currently under construction. This work compares experimental data from a TOF SEMSANS setup, where a spatial beam modulation of a white beam is obtained using triangular field coils, with Monte Carlo ray‐tracing simulations. The experiments and simulations in accordance demonstrate that a good contrast can be achieved when using a constant field in the triangular coils. In the reported setup only neutrons with certain wavelengths rotate by a Larmor precession angle that spatially modulates their polarization to coincide with the period of a grating installed at the detector position. This is shown by measuring with a broad wavelength range while scanning the echo condition.